AAV variant enables human T cell engineering in vivo - Lu, Zhike; Ni, Ke; Liu, Wenjun; Song, Qingkai; Zheng, Rong; Wei, Ming; Zhang, Yinling; Wang, Jing; Wei, Lina; Wu, Chenlu; Zhang, Qingfeng; Wu, Jiamei; et al. (LangTaoSha Preprint Server, 2026)
Autologous chimeric antigen receptor T (CAR-T) cell therapy has demonstrated therapeutic effectiveness in hematologic malignancies and autoimmune diseases. However, the manufacturing complexity and the required lymphodepletion hindered its wide clinical application. Engineering human T cells in vivo holds promise to conquer these limitations but requires effective T cell-targeted CAR delivery with demonstrated safety. Here, we show that an engineered AAV6 variant, AAV6-M2, can enable in vivo CAR expression in human T cells following systemic administration in a Humanized Immune System (HIS) mouse model. AAV6-M2-CD19CAR turned up to 85.2% of human CD8+ T cells into CAR-T cells across multiple organs six weeks post-AAV injection. In HIS mice exhibiting systemic lupus erythematosus (SLE)-like symptoms, AAV6-M2-CD19CAR treatment effectively depleted B cells in both peripheral blood and tissues, accompanied by improved lupus pathologies. Importantly, systemic delivery of AAV6-M2 resulted in significant liver de-targeting, with viral genome levels in the liver reduced by over two orders of magnitude in both mice and cynomolgus macaque compared to the wild-type AAV. Through CRISPR screening, cryo-EM structural analysis, and molecular docking, we identified CD62L as a key mediator of AAV6-M2’s enhanced transduction to human T cells, enabling CAR delivery without the need for prior T cell activation. These findings established that AAV-mediated CAR delivery can generate functional human CAR-T cells in vivo, with mechanistic insights into the selective targeting of T cells. This work highlights engineered AAV vectors as a promising platform for in vivo CAR-T therapy and expands the therapeutic landscape of AAV beyond inherited diseases.